Analisis Rantai Pasok (Supply Chain Management) Pada Penjualan Salak di Dusun Salakan Desa Semboro Kecamatan Semboro Kabupaten Jember - Rofika, Choiriyatur; Pudjiastutik, Endang Wahyu (KUBIS, 2022)
Salak is one of the commodities that exist in Indonesia which was developed around the 1980s with sweet and crunchy. Jember Regency is one of the salak producers, precisely in Salakan Hamlet in Semboro Village, where 95% of the people produce salak. The aims of this research are (1). To find out supply chain activities on salak in Salakan Hamlet, (2). To find out the existing marketing margin for Salak in Salakan Hamlet, (3). To find out the efficiency of the Salak Marketing Channel in Salakan Hamlet. The sampling method used in this study is the random sampling method. The results of this study indicate that 1) Marketing channels in Dusun Salakan has 2 channels, namely: Channel I (producer-retailer-consumer), Channel II (producer-collector-traders-retailer-consumer). 2) Margins for each marketing channel I are 1500/kg, while the margins for channel II are 1500 and 2500/kg. 3) the marketing channel in salak which has the most efficient level of efficiency is channel I which is 8.33%. And the highest or most inefficient is channel  II  by 9.74%. So an effective supply chain is to use a short marketing chain so that marketing costs can be suppressed and marketing profits are higher.